Fluorine-doped porous lithium iron manganese phosphate and preparation method thereof, positive electrode and battery

The porous structure of lithium iron manganese phosphate formed by fluorine doping and pore formation treatment solves the problem of limited rate performance and significantly improves electrochemical performance and structural stability.

CN116443842BActive Publication Date: 2025-03-25DONGGUAN CHAM BATTERY TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310419722.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-18
Publication Date
2025-03-25
Estimated Expiration
2043-04-18

AI Technical Summary

Technical Problem

The ionic and electron conductivity of lithium iron manganese phosphate materials is low and the electrochemical activity is insufficient, resulting in limited rate performance.

Method used

Through fluorine doping and pore formation treatment, lithium iron manganese phosphate with a porous structure is formed, which inhibits the dissolution of manganese, and stabilizes the crystal lattice by doping metal fluoride, thereby improving the ion migration ability.

Benefits of technology

The rate performance of lithium iron manganese phosphate is significantly improved, the lattice distortion of manganese during charging and discharging is reduced, and the electrochemical performance is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004190895760000121
    Figure BDA0004190895760000121
  • Figure HDA0004190895770000011
    Figure HDA0004190895770000011
  • Figure HDA0004190895770000012
    Figure HDA0004190895770000012
Patent Text Reader

Abstract

The present invention relates to the field of batteries, and in particular to a fluorine-doped porous lithium iron manganese phosphate and a preparation method thereof, a positive electrode and a battery. The present invention provides a fluorine-doped porous lithium iron manganese phosphate having a structure of formula I; LiFe 1‑x Mn x PO 4‑(y / 2) F y Formula I; x is 0.3 to 0.7; y is 0.001 to 0.03. In the three carbon doping methods adopted by the present invention, after the first heat treatment of the carbon source, gas volatilization is formed, and pores are formed inside the particles to improve the interface between the manganese iron phosphate and the electrolyte, and to improve the interfacial migration ability of lithium ions; while the particles are being pore-formed, metal fluoride doping is used to stabilize the lattice, improve the intrinsic migration of ions, and reduce the lattice distortion of manganese during the charging and discharging process, so that the manganese iron phosphate lithium obtains excellent performance. The production process of the present invention is basically equivalent to the process route of preparing manganese iron phosphate lithium from iron phosphate, and the equipment is universal and can be mass-produced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of batteries, in particular to a fluorine-doped porous lithium iron manganese phosphate and a preparation method thereof, a positive electrode and a battery. Background Art

[0002] As an upgraded version of lithium iron phosphate, lithium iron manganese phosphate has received increasing attention in the lithium-ion battery industry. Compared with lithium iron phosphate, the use of manganese to replace iron to form an iron-manganese-lithium solid solution can ensure that the capacity is basically equivalent to that of lithium iron phosphate, while increasing the voltage platform, thereby breaking through the bottleneck of lithium iron phosphate in energy density and increasing the proportion by 15-20%. Moreover, the material manufacturing process is basically the same as that of lithium iron phosphate, and the cost is mainly the replacement of iron by manganese. Therefore, it is relatively simple for material factories and can be applied on a large scale.

[0003] However, compared with lithium iron phosphate materials, lithium iron manganese phosphate has a similar structure, both of which are olivine structures, but its ionic and electronic conductivity is far inferior to that of lithium iron phosphate, and its electrochemical inertness, coupled with the JT effect leading to lattice distortion affecting lithium deintercalation, so the capacity of lithium iron manganese phosphate materials is severely limited, and the rate performance is severely limited. Based on this, improving the conductivity of electrons and ions, increasing electrochemical activity, enhancing structural stability during charge and discharge, forming a porous structure, and promoting lithium ion migration and diffusion through nano-sizing, doping, carbon coating and other means have become the key to developing high-rate iron manganese phosphate materials and meeting market demand.

[0004] Compared with CN 107732176 A, this invention mainly forms a lithium iron phosphate manganese lithium precursor solution and a conductive carbon coating layer solution, mixes, grinds, dries and sinters, and carbon-coates the primary and secondary particles of the lithium iron manganese phosphate to form highly conductive lithium iron manganese phosphate. However, it does not solve the problem of poor cycling caused by the lattice distortion caused by the JT effect of manganese, and there is less carbon residue on the surface of the particles, and the final electrochemical performance is different from expectations. Summary of the invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide a fluorine-doped porous lithium iron manganese phosphate and a preparation method thereof, a positive electrode and a battery. The preparation method provided by the present invention performs pore formation and fluorine doping while preparing the lithium iron manganese phosphate positive electrode material, which can inhibit the manganese dissolution of the obtained lithium iron manganese phosphate positive electrode material and improve its rate performance.

[0006] The present invention provides a fluorine-doped porous lithium iron manganese phosphate having a structure of formula I;

[0007] LiFe 1-x Mn x PO 4-(y / 2) F y Formula I;

[0008] The value of x is 0.3 to 0.7;

[0009] The value of y is 0.001~0.03.

[0010] The fluorine-doped porous lithium iron manganese phosphate provided by the present invention is doped with metal fluorides, which is beneficial to stabilizing the lattice, improving the intrinsic migration of ions, and reducing the lattice distortion of manganese during the charging and discharging process, thereby enabling the lithium iron manganese phosphate to obtain excellent performance.

[0011] The fluorine-doped porous lithium iron manganese phosphate provided by the present invention has a porous structure, which can promote the migration and diffusion of lithium ions. In some embodiments of the present invention, the porosity of the fluorine-doped porous lithium iron manganese phosphate is 50% to 85%.

[0012] The fluorine-doped porous lithium iron manganese phosphate provided by the present invention comprises primary particles, secondary particles and carbon coated on the primary particles and the secondary particles, and its specific structure is shown in Formula II: LiFe 1-x Mn x PO 4-(y / 2) F y @C formula II; x is 0.3 to 0.7; y is 0.001 to 0.03. The primary particles of the present invention are fluorine-doped porous lithium iron manganese phosphate, and the particle size of the primary particles is 0.05 μm to 0.2 μm; the secondary particles are formed by agglomeration of the primary particles, and the particle size of the secondary particles is 3 μm to 16 μm; the carbon is in-situ coated on the primary particles and uniformly coated on the surface of the secondary particles.

[0013] The fluorine-doped porous lithium iron manganese phosphate provided by the present invention forms a spherical morphology with porous primary particles, and a conductive network between primary particles and on the surface of secondary particles, which inhibits the dissolution of manganese. In addition, the doping of F metal compounds reduces the lattice distortion and migration of lithium ions during the charging and discharging process, greatly improving high-rate discharge. In certain embodiments of the present invention, the fluorine-doped porous lithium iron manganese phosphate of the present invention has a discharge capacity of more than 145 mAh at 10C discharge. In certain embodiments of the present invention, the tap density of the fluorine-doped porous lithium iron manganese phosphate of the present invention is 0.6 g / cc to 1.3 g / cc. In certain embodiments of the present invention, the specific surface area of ​​the fluorine-doped porous lithium iron manganese phosphate of the present invention is 16 m 2 / g~22m 2 / g.

[0014] The present invention also provides a method for preparing fluorine-doped porous lithium iron manganese phosphate, comprising the following steps:

[0015] The manganese iron phosphate, a pore-forming agent, a fluorine source and a lithium source are mixed and heat-treated to obtain fluorine-doped porous manganese iron lithium phosphate.

[0016] Specifically, the method for preparing fluorine-doped porous lithium iron manganese phosphate of the present invention comprises the following steps: step S1) subjecting manganese iron phosphate, a pore-forming agent and a fluorine source to a first heat treatment in a solvent to obtain fluorine-doped porous manganese iron phosphate;

[0017] Step S2) subjecting the fluorine-doped porous manganese iron phosphate, additives, lithium source and first carbon source in step S1) to a second heat treatment in a solvent to obtain a fluorine-doped porous manganese iron phosphate lithium precursor;

[0018] Step S3) reacting the second carbon source with the lithium iron manganese phosphate precursor of step S2) to obtain fluorine-doped porous lithium iron manganese phosphate.

[0019] The present invention first prepares fluorine-doped porous manganese iron phosphate. Specifically, the present invention performs a first heat treatment on manganese iron phosphate, a pore-forming agent and a fluorine source in a solvent to obtain fluorine-doped porous manganese iron phosphate. More specifically, the present invention disperses manganese iron phosphate, a pore-forming agent and a fluorine source in a solvent, mixes and stirs, and then grinds and spray-dries, and performs a first heat treatment on the resulting product to obtain fluorine-doped porous manganese iron phosphate. In certain embodiments of the present invention, the present invention disperses manganese iron phosphate, a pore-forming agent and a fluorine source in a solvent, mixes and stirs, and then sequentially performs coarse grinding, fine grinding and spray drying, and performs a first heat treatment on the product obtained after spray drying to obtain fluorine-doped porous manganese iron phosphate.

[0020] The present invention first disperses manganese iron phosphate, a pore-forming agent and a fluorine source in a solvent and mixes and stirs; the mixing and stirring rate is 10 Hz to 50 Hz, and the mixing and stirring time is 0.5 h to 3 h. The iron-manganese ratio in the manganese iron phosphate of the present invention is (3:7) to (7:3), preferably (4:6) to (6:4); the particle size D50 of the manganese iron phosphate is ≤10 μm, preferably the particle size D50 is ≤5 μm; the tap density of the manganese iron phosphate is 0.5 g / cc to 1.2 g / cc, preferably 0.6 g / cc to 0.9 g / cc; the specific surface area of ​​the manganese iron phosphate is ≤9 m 2 / g. The pore-forming agent of the present invention is selected from one or more combinations of glucose, sucrose, starch, cellulose and lemon sugar; the fluorine source is a metal fluoride, specifically selected from one or more combinations of LiF, MgF2, AlF3, NaF, CaF2 and KF; the solvent is selected from one or more combinations of pure water, ethanol, acetone, methanol and tetrahydrofuran. In certain embodiments of the present invention, the molar ratio of the manganese iron phosphate and the fluorine source is 1: (0.001-0.03), and the mass of the pore-forming agent is 5%-50% of the mass of the manganese iron phosphate, preferably 5%-30%. In certain embodiments of the present invention, the solid content of the manganese iron phosphate, pore-forming agent and fluorine source in the solvent is 10%-60%.

[0021] The present invention disperses manganese iron phosphate, a pore-forming agent and a fluorine source in a solvent and mixes and stirs them, and then grinds the product obtained by the mixing and stirring; specifically, the grinding is coarse grinding and fine grinding in sequence. The coarse grinding described in the present invention is coarse grinding while stirring, which can enhance the uniformity of each material, and the stirring speed during coarse grinding is 10Hz to 40Hz. The present invention uses zirconium beads with a particle size of 1μm to 4μm for coarse grinding, and the rotation speed of the coarse grinding is 200RPM to 700RPM, and the particle size of the product obtained after coarse grinding is less than 1.0μm. The fine grinding described in the present invention is fine grinding while stirring, and the stirring speed during fine grinding is 10Hz to 40Hz. The present invention uses zirconium beads with a particle size of 0.01μm to 0.4μm for fine grinding, and the rotation speed of the fine grinding is 300RPM to 800RPM, and the particle size of the product obtained after fine grinding is 0.05μm to 0.5μm.

[0022] In the present invention, the product obtained by mixing and stirring is ground, and then the ground product is spray-dried. The air inlet temperature of the spray drying of the present invention is 170°C to 270°C, and the air outlet temperature of the spray drying is 80°C to 160°C. In certain embodiments of the present invention, the particle size of the product obtained after the spray drying of the present invention is less than 12 μm.

[0023] The present invention subjects the product obtained after spray drying to a first heat treatment to obtain fluorine-doped porous manganese iron phosphate. In certain embodiments of the present invention, the present invention subjects 1 kg to 10 kg of the product obtained after spray drying to a first heat treatment to obtain fluorine-doped porous manganese iron phosphate. The first heat treatment of the present invention is carried out in an air or oxygen atmosphere. In one embodiment, the temperature of the first heat treatment is 200°C to 650°C; the time of the first heat treatment is 1h to 9h.

[0024] After the fluorine-doped porous manganese iron phosphate is prepared by the present invention, it is used to prepare a fluorine-doped porous manganese iron phosphate lithium precursor. Specifically, the present invention subjects the above-obtained fluorine-doped porous manganese iron phosphate, additives, lithium source and first carbon source to a second heat treatment in a solvent to obtain a fluorine-doped porous manganese iron phosphate lithium precursor. More specifically, the present invention disperses the above-obtained fluorine-doped porous manganese iron phosphate, additives, lithium source and first carbon source in a solvent and mixes and stirs, then grinds and spray-dries, and subjects the resulting product to a second heat treatment to obtain a fluorine-doped porous manganese iron phosphate lithium precursor. In certain embodiments of the present invention, the present invention disperses the above-obtained fluorine-doped porous manganese iron phosphate, additives, lithium source and first carbon source in a solvent and mixes and stirs, then sequentially performs coarse grinding, fine grinding and spray drying, and subjects the resulting product after spray drying to a second heat treatment to obtain a fluorine-doped porous manganese iron phosphate lithium precursor.

[0025] The present invention first disperses the fluorine-doped porous manganese iron phosphate, additives, lithium source and first carbon source obtained above in a solvent and mixes and stirs; the mixing and stirring rate is 10Hz to 50Hz, and the mixing and stirring time is 0.5h to 3h. In certain embodiments of the present invention, the additive is a compound of a rare metal element, specifically at least one of a Nb compound, a W compound, a Ti compound or a Sb compound; the lithium source is selected from one or more combinations of lithium carbonate, lithium hydroxide, lithium hydroxide monohydrate, lithium oxalate or lithium nitrate; the first carbon source is selected from one or more combinations of glucose, starch, epoxy resin, phenolic resin, starch, sucrose, cellulose, lemon sugar, graphite or carbon tube; the solvent is selected from one or more combinations of deionized water, ethanol and acetone. In certain embodiments of the present invention, the molar ratio of the fluorine-doped porous manganese iron phosphate, the additive and the lithium source is 1: (0.001-0.02): (1.02-1.10), and the mass amount of the first carbon source is 5%-40% of the fluorine-doped porous manganese iron phosphate. In certain embodiments of the present invention, the solid content of the fluorine-doped porous manganese iron phosphate, the additive, the lithium source and the first carbon source in the solvent is 10%-60%.

[0026] The present invention disperses the fluorine-doped porous manganese iron phosphate, additives, lithium source and first carbon source obtained above in a solvent and mixes and stirs, and then grinds the product obtained by mixing and stirring; specifically, the grinding is coarse grinding and fine grinding in sequence. The coarse grinding of the present invention is coarse grinding while stirring, which can enhance the uniformity of each material, and the stirring speed during coarse grinding is 10Hz to 40Hz. The present invention uses zirconium beads with a particle size of 1μm to 4μm for coarse grinding, the rotation speed of the coarse grinding is 200RPM to 700RPM, and the particle size of the product obtained after coarse grinding is less than 1.0μm. The fine grinding of the present invention is fine grinding while stirring, and the stirring speed during fine grinding is 10Hz to 40Hz. The present invention uses zirconium beads with a particle size of 0.01μm to 0.4μm for fine grinding, the rotation speed of the fine grinding is 300RPM to 800RPM, and the particle size of the product obtained after fine grinding is 0.010μm to 0.25μm.

[0027] In the present invention, the product obtained by mixing and stirring is ground, and then the ground product is spray-dried. The air inlet temperature of the spray drying of the present invention is 170°C to 270°C, and the air outlet temperature of the spray drying is 80°C to 140°C. In certain embodiments of the present invention, the particle size of the product obtained after the spray drying of the present invention is less than 7 μm.

[0028] The present invention subjects the product obtained after spray drying to a second heat treatment to obtain a fluorine-doped porous lithium iron manganese phosphate precursor. In certain embodiments of the present invention, the present invention subjects 1kg to 7kg of the product obtained after spray drying to a second heat treatment to obtain a fluorine-doped porous lithium iron manganese phosphate precursor. The second heat treatment of the present invention is carried out in an atmosphere of one or a combination of nitrogen, argon or helium. In one embodiment, the temperature of the second heat treatment is 600°C to 820°C; the time of the second heat treatment is 5h to 20h.

[0029] After the fluorine-doped porous manganese iron lithium phosphate precursor is prepared in the present invention, it is used to prepare fluorine-doped porous manganese iron lithium phosphate. Specifically, the present invention reacts the second carbon source with the above-obtained manganese iron lithium phosphate precursor to obtain fluorine-doped porous manganese iron lithium phosphate. In certain embodiments of the present invention, the present invention performs a vapor deposition reaction on the second carbon source and the above-obtained manganese iron lithium phosphate precursor in a carrier gas, removes iron, and sieves to obtain fluorine-doped porous manganese iron lithium phosphate. In certain embodiments of the present invention, the second carbon source is selected from at least one of methane or acetylene; the carrier gas is selected from at least one of nitrogen or helium. In certain embodiments of the present invention, the volume ratio of the second carbon source to the carrier gas is (1.3-4): 1. In certain embodiments of the present invention, the temperature of the vapor deposition reaction is 600°C-820°C; the time of the vapor deposition is 2h-20h. The iron removal of the present invention, also known as demagnetization, is carried out by an electromagnet, and the Gauss value is 10000GS-30000GS. The screening of the present invention is carried out using a sieve of 200 to 500 meshes.

[0030] The preparation method of fluorine-doped porous lithium iron manganese phosphate provided by the present invention mainly controls the crystal structure, primary particle size and shape, secondary particle size, and particle surface, and implements carbon-doped pores, doping, one grinding, one spray drying, and one heat treatment on the manganese iron phosphate by means of three carbon-doping, two grindings, and metal fluoride doping. Then, carbon doping, adding a lithium source, secondary grinding, secondary spray drying, secondary heat treatment, and then CVD carbon coating are performed to finally synthesize a high-rate fluorine-doped porous lithium iron manganese phosphate material.

[0031] The present invention also provides a positive electrode, including the fluorine-doped porous lithium iron manganese phosphate or the fluorine-doped porous lithium iron manganese phosphate prepared by the above-mentioned preparation method. The present invention also provides a battery, including the above-mentioned positive electrode. Specifically, the battery provided by the present invention is a lithium ion battery, including a positive electrode, a negative electrode, a separator and an electrolyte; the positive electrode is the positive electrode mentioned above. The negative electrode, separator and electrolyte described in the present invention are the negative electrode, separator and electrolyte that can be used in lithium ion batteries and are well known to those skilled in the art.

[0032] The present invention provides a fluorine-doped porous lithium iron manganese phosphate having a structure of formula I; LiFe1-x Mn x PO 4-(y / 2) F y Formula I; x is 0.3 to 0.7; y is 0.001 to 0.03. The three carbon dopings adopted by the present invention, after the first carbon source heat treatment, gas volatilization is formed, and pores are formed inside the primary particles, the interface between iron manganese phosphate and the electrolyte is improved, and the interface migration ability of lithium ions is improved; the second carbon doping plays a reducing role, inhibits the growth of primary particles, and in-situ carbon coating is performed on the primary particles; the three carbon dopings are CVD carbon coating, and a carbon layer is uniformly coated on the surface of the secondary particles to improve the conductivity, and finally a complete conductive network is formed between the primary particles, between the secondary particles, and between the primary particles and the secondary particles, thereby reducing manganese dissolution. The present invention uses metal fluoride doping while forming pores in the primary particles, which is beneficial to stabilize the lattice, improve the intrinsic migration of ions, and reduce the lattice distortion of manganese during the charging and discharging process, so that the iron manganese lithium phosphate obtains excellent performance. The two grindings of the present invention are ultrafine grinding, which reduces the size of the primary particles, reduces the difficulty of grinding, improves the consistency of the primary particles, greatly optimizes and improves its conductivity, reduces the migration distance of lithium ions, and improves electrical properties. The invention adopts spray drying to perform secondary granulation to form a spherical shape, which improves the tap density. The invention is basically equivalent to the process route of preparing lithium iron manganese phosphate from iron phosphate in production process, and the equipment is universal and can be mass-produced. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a process flow chart of the fluorine-doped porous lithium iron manganese phosphate of the present invention;

[0034] Figure 2 This is a scanning electron microscope image of the high-magnification fluorine-doped porous lithium iron manganese phosphate material obtained in Example 1. DETAILED DESCRIPTION

[0035] The present invention discloses a fluorine-doped porous lithium iron manganese phosphate and a preparation method thereof, a positive electrode and a battery. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all deemed to be included in the present invention. The method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the method and application of this article without departing from the content, spirit and scope of the present invention to realize and apply the technology of the present invention.

[0036] The fluorine-doped porous lithium iron manganese phosphate of the present invention is Figure 1 The process flow chart shown is used for preparation. Figure 1 This is a process flow chart of the fluorine-doped porous lithium iron manganese phosphate of the present invention.

[0037] The present invention will be further described below in conjunction with embodiments:

[0038] Example 1

[0039] Step 1) 15 kg of sucrose was weighed and put into a feeding tank containing 425 kg of pure water. The stirring speed was set to 20 Hz. After stirring for 10 min, 300 kg of manganese iron phosphate and 0.052 kg of LiF were added in sequence. The molecular formula of the manganese iron phosphate added was Fe 0.4 Mn 0.6 PO4, particle size 3.5μm, specific surface area 3m 2 / g, tap density is 0.75g / cc, stirring is continued for 50min, then coarse grinding is performed, the zirconium ball used for coarse grinding is 1.0μm, the stirring speed during coarse grinding is 30HZ, the speed of the sand mill for coarse grinding is 500RPM, the coarse grinding time is 2.0h, and the particle size after coarse grinding is 1.2μm; fine grinding is performed, the zirconium ball used for fine grinding is 0.05μm, the stirring speed during fine grinding is 30HZ, the speed of the sand mill for fine grinding is 600RPM, the fine grinding time is 1.0h, and the particle size after fine grinding is 0.5μm, to obtain slurry A. The slurry A is spray dried, the air inlet temperature is 230℃, and the air outlet temperature is 100℃, to obtain dried material A, the particle size of the dried material A is 8μm. The dried material A was put into a kiln in a bowl with a loading amount of 7 kg for heat treatment. The atmosphere of the kiln was air. The kiln heat treatment temperature was 480° C. for 3 hours, and the heat-treated material A was harvested.

[0040] Step 2) 314.5 kg of heat-treated material A, 0.64 kg of TiO2, 78 kg of lithium carbonate, and 36 kg of starch are put into 580 kg of pure water for mixing, stirred at a stirring speed of 35 Hz for 1.5 h, and then turned to coarse grinding, the zirconium ball used for coarse grinding is 1.5 μm, the stirring speed during coarse grinding is 25 Hz, the speed of the coarse grinding sand mill is 550 RPM, the coarse grinding time is 3.0 h, and the particle size after coarse grinding is 0.78 μm; turned to fine grinding, the zirconium ball used for fine grinding is 0.05 μm, The stirring speed during fine grinding is 25HZ, the speed of the sand mill for fine grinding is 660RPM, the fine grinding time is 4h, and the particle size after fine grinding is 0.13μm to obtain slurry B; the slurry B is spray granulated at an inlet air temperature of 230°C and an outlet air temperature of 100°C to obtain dry material B, and the particle size of the dry material B is 4.8μm; the dry material B is put into the kiln for heat treatment with a loading amount of 3.5kg, the kiln atmosphere is nitrogen, the kiln heat treatment temperature is 630°C, and the heat treatment time is 6h to obtain heat-treated material B.

[0041] Step 3) The heat-treated material B obtained in step 2) is transferred to a CVD furnace, and nitrogen and acetylene are introduced at a volume ratio of 1:1.7. The vapor deposition temperature is 610°C for 2 hours, and then demagnetized with a 20000GS electromagnet, and passed through a 300-mesh sieve to obtain a high-rate fluorine-doped porous lithium iron manganese phosphate material. The obtained high-rate fluorine-doped porous lithium iron manganese phosphate material is characterized by scanning electron microscopy, as shown in FIG. Figure 2 As shown, Figure 2 This is a scanning electron microscope image of the high-magnification fluorine-doped porous lithium iron manganese phosphate material obtained in Example 1.

[0042] Example 2

[0043] Compared with Example 1, the difference is:

[0044] Step 1) Add the molecular formula Fe 0.4 Mn 0.6 The formula of PO4 iron manganese phosphate is changed to Fe 0.5 Mn 0.5 PO4 iron manganese phosphate;

[0045] Step 2) The fine grinding time was changed to 8 hours, and the particle size after fine grinding was 0.06 μm; the particle size of the dried material B was 3.7 μm.

[0046] Example 3

[0047] Compared with Example 1, the difference is:

[0048] Step 1) 15 kg of sucrose was replaced with 10 kg of starch, the atmosphere of the kiln was changed to pure oxygen, the heat treatment temperature was changed to 450°C, and the time was 1.7 h;

[0049] Step 2) 78 kg of lithium carbonate was replaced by 86 kg of lithium hydroxide monohydrate, the fine grinding time was changed to 5.6 h, and the particle size after fine grinding was 0.17 μm; the particle size of the dried material B was 3.7 μm; the heat treatment temperature in the kiln was changed to 600 ° C, and the time was changed to 8 h.

[0050] Example 4

[0051] Compared with Example 1, the difference is:

[0052] Step 1) The molecular formula is Fe 0.4 Mn 0.6 The formula of PO4 iron manganese phosphate is changed to Fe 0.6 Mn 0.4 For PO4 iron manganese phosphate, the grinding time was changed to 2.6h, and the particle size after grinding was 0.33μm; the particle size of dried material A was changed to 6.8μm; the kiln heat treatment temperature was 500℃, and the time was 2h;

[0053] Step 2) The coarse grinding particle size was changed to 0.65 μm, the fine grinding time was 3.2 h, and the particle size after fine grinding was 0.17 μm; the particle size of the dried material B was 4.2 μm;

[0054] Step 3) Change the vapor deposition temperature to 670°C and the time to 3.5h.

[0055] Example 5

[0056] Compared with Example 1, the difference is:

[0057] Step 2) 0.64 kg of TiO2 was replaced with 0.412 kg of Nb2O5, and 36 kg of starch was replaced with 300 kg of glucose;

[0058] Step 3) The nitrogen and acetylene introduced in a volume ratio of 1:1.7 was replaced by nitrogen and methane introduced in a volume ratio of 1:2.

[0059] Comparative Example 1

[0060] Step 1) 300 kg of manganese ferrous phosphate, 0.64 kg of TiO2, 78 kg of lithium carbonate and 36 kg of starch were weighed and put into 580 kg of pure water for mixing. The molecular formula of the manganese ferrous phosphate added was Fe 0.4 Mn 0.6 PO4, particle size is 3.5μm, specific surface area is 3m 2 / g, tap density is 0.75g / cc, stirring is carried out at a stirring speed of 35HZ for 1.5h, then coarse grinding is started, the zirconium ball used for coarse grinding is 1.0μm, the stirring speed during coarse grinding is 25HZ, the speed of the sand mill for coarse grinding is 550RPM, the coarse grinding time is 3.0h, the particle size after coarse grinding is 1.1μm, then fine grinding is started, the zirconium ball used for fine grinding is 0.05μm, the stirring speed during fine grinding is 25HZ, and the fine grinding is The sand mill speed is 660RPM, the fine grinding time is 7h, the particle size after fine grinding is 0.19μm, and a slurry is obtained. The slurry is spray granulated at an inlet air temperature of 230°C and an outlet air temperature of 100°C to obtain a dry material with a particle size of 4.8μm. The dry material is put into a kiln for heat treatment with a loading amount of 3.5kg. The kiln atmosphere is nitrogen, the kiln temperature is 630°C, and the time is 6h to obtain a heat-treated material.

[0061] Step 2) The heat-treated material is transferred to a CVD furnace, and nitrogen and acetylene are introduced in a volume ratio of 1:1.7. The vapor deposition temperature is 610°C for 2 hours, and then demagnetized with a 20000GS electromagnet and passed through a 300-mesh sieve to obtain a lithium iron manganese phosphate material.

[0062] Comparative Example 2

[0063] Step 1) Weigh 15 kg of sucrose and put it into a feeding tank containing 425 kg of pure water. Set the stirring speed to 20 Hz. After stirring for 10 minutes, add 300 kg of manganese ferrous phosphate. The molecular formula of the manganese ferrous phosphate is Fe 0.4 Mn 0.6 PO4, particle size is 3.5μm, specific surface area is 3m 2 / g, tap density is 0.75g / cc, continue stirring for 50min, then turn to coarse grinding, the zirconium ball used for coarse grinding is 1.0μm, the stirring speed during coarse grinding is 30HZ, the speed of the sand mill for coarse grinding is 500RPM, the coarse grinding time is 2.0h, the particle size after coarse grinding is 1.2μm, turn to fine grinding, the zirconium ball used for fine grinding is 0.05μm, the stirring speed during fine grinding is 30HZ, the speed of the sand mill for fine grinding is 600RPM, the fine grinding time is 1.0h, the particle size after fine grinding is 0.5μm, and slurry A is obtained. The slurry A is spray dried, the inlet air temperature is 230℃, and the outlet air temperature is 100℃, to obtain dried material A, the particle size of the dried material A is 8μm. The dried material A is put into the kiln with a loading amount of 7kg, the atmosphere of the kiln is air, the kiln heat treatment temperature is 480℃, the time is 3h, and the heat-treated material A is harvested.

[0064] Step 2) 299.7 kg of heat-treated material A and 0.052 kg of LiF were put into 400 kg of pure water, stirred at a speed of 35 Hz for 1.0 h, and then dried in a spray dryer with an inlet air temperature of 270° C. and an outlet air temperature of 120° C. After drying, 7.0 kg of the material was heat-treated in a kiln in an air atmosphere at a kiln heat treatment temperature of 480° C. for 3 h to obtain heat-treated material B.

[0065] Step 3) 313.6 kg of heat-treated material B, 0.64 kg of TiO2, 78 kg of lithium carbonate and 36 kg of starch were put into 580 kg of pure water for mixing, the stirring speed was 35 Hz, the stirring time was 1.5 h, and then the mixture was coarsely ground, the zirconium ball used for coarse grinding was 1.5 μm, the stirring speed during coarse grinding was 25 Hz, the sand mill speed for coarse grinding was 550 RPM, the coarse grinding time was 3.0 h, the particle size after coarse grinding was 0.78 μm, and the mixture was finely ground, and the zirconium ball used for fine grinding was 0.05 μm. m, the stirring speed during fine grinding is 25HZ, the speed of the sand mill for fine grinding is 660RPM, the fine grinding time is 4h, the particle size after fine grinding is 0.13μm, and slurry C is obtained. The slurry C is spray granulated at an inlet air temperature of 230℃ and an outlet air temperature of 100℃ to obtain dry material C. The particle size of the dry material C is 4.8μm. The dry material C is put into a kiln for heat treatment with a loading amount of 3.5kg. The kiln atmosphere is nitrogen, the kiln temperature is 630℃, and the time is 6h to obtain heat-treated material C.

[0066] Step 4) The heat-treated material C is transferred to a CVD furnace, and nitrogen and acetylene are introduced in a volume ratio of 1:1.7. The vapor deposition temperature is 610°C for 2 hours, and then demagnetized with a 20000GS electromagnet and passed through a 300-mesh sieve to obtain a lithium iron manganese phosphate material.

[0067] The lithium manganese iron phosphate materials obtained in the above examples 1 to 5 and comparative examples 1 to 2 were characterized and tested for performance, and the test data are shown in Table 1:

[0068] Table 1

[0069]

[0070] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A fluorine-doped porous lithium iron manganese phosphate having a structure of formula I; LiFe 1-x Mn x PO 4-(y / 2) F y Formula I; The value of x is 0.3~0.7; The value of y is 0.001~0.03; The preparation method of the fluorine-doped porous lithium iron manganese phosphate comprises the following steps: Step S1) subjecting manganese iron phosphate, a pore-forming agent and a fluorine source to a first heat treatment in a solvent to obtain fluorine-doped porous manganese iron phosphate; Step S2) subjecting the fluorine-doped porous manganese iron phosphate, additives, lithium source and first carbon source in step S1) to a second heat treatment in a solvent to obtain a fluorine-doped porous manganese iron phosphate lithium precursor; Step S3) reacting the second carbon source with the lithium iron manganese phosphate precursor in step S2) to obtain fluorine-doped porous lithium iron manganese phosphate.

2. The fluorine-doped porous lithium iron manganese phosphate according to claim 1, characterized in that: The porosity of the fluorine-doped porous lithium iron manganese phosphate is 50% to 85%.

3. The fluorine-doped porous lithium iron manganese phosphate according to claim 1, characterized in that: It includes primary particles, secondary particles and carbon coated on the primary particles and the secondary particles; The primary particles are the fluorine-doped porous lithium iron manganese phosphate; The secondary particles are formed by agglomeration of the primary particles.

4. The fluorine-doped porous lithium iron manganese phosphate according to claim 3, characterized in that: The particle size of the primary particles is 0.05 μm to 0.2 μm; The particle size of the secondary particles is 3 μm to 16 μm.

5. A method for preparing fluorine-doped porous lithium iron manganese phosphate, characterized in that: The following steps are involved: Step S1) subjecting manganese iron phosphate, a pore-forming agent and a fluorine source to a first heat treatment in a solvent to obtain fluorine-doped porous manganese iron phosphate; Step S2) subjecting the fluorine-doped porous manganese iron phosphate, additives, lithium source and first carbon source in step S1) to a second heat treatment in a solvent to obtain a fluorine-doped porous manganese iron phosphate lithium precursor; Step S3) reacting the second carbon source with the lithium iron manganese phosphate precursor in step S2) to obtain fluorine-doped porous lithium iron manganese phosphate.

6. The preparation method according to claim 5, characterized in that: In step S1), the fluorine source is selected from one or more of LiF, MgF2, AlF3, NaF, CaF2 or KF; The pore-forming agent is selected from one or more of glucose, sucrose, starch, cellulose or citric acid.

7. The preparation method according to claim 5, characterized in that: In step S1), the molar ratio of the manganese iron phosphate to the fluorine source is 1:(0.001-0.03), and the amount of the pore former is 5 wt%-50 wt% of the amount of the manganese iron phosphate.

8. A positive electrode, characterized in that The invention comprises the fluorine-doped porous lithium iron manganese phosphate as described in any one of claims 1 to 4 or the fluorine-doped porous lithium iron manganese phosphate prepared by the preparation method as described in any one of claims 5 to 7.

9. A battery, characterized in that: Comprising the positive electrode as claimed in claim 8.

Citation Information

Patent Citations

  • Preparation method of lithium ion battery positive electrode nano-material

    CN107732176A

  • Multielement doped lithium phosphate anode material and preparation method

    CN104037411A

  • Fluorine-doped lithium ferric manganese phosphate cathode material and preparation method thereof

    CN105470468A

  • Porous lithium phosphate metal salt and method for preparing the same

    US20130146806A1